Drivers of Recreational Angler Satisfaction in Port Phillip Bay, Australia - Ali Jalali; Justin D. Bell; Harry K. Gorfine; Simon D. Conron (Fisheries Management and Ecology, 2025)
As a widely enjoyed pursuit, recreational fishing plays a key socio‐economic role in Australia by supporting coastal businesses, especially in regional areas. Satisfaction is considered an end outcome of angling that is important in fisheries management by contributing to ongoing participation and regulatory strategies. Port Phillip Bay (PPB) in Victoria, Australia, hosts the State's largest marine recreational fishery, yet angler satisfaction has not been previously explored. We evaluated the influence of age groups, regions (5 boat ramps in Melbourne, 7 in Bellarine, and 8 in Mornington), key target species (snapper, King George whiting, calamari, and flathead), and catch rate on spatiotemporal patterns in long‐term satisfaction from creel surveys conducted around PPB during 2016–2022. Angler satisfaction varied with catch per unit of effort (CPUE) and angler avidity. Satisfaction varied annually and regionally, with higher satisfaction among younger anglers, especially in the Bellarine region along the western coastline of PPB. Angler satisfaction also varied among target species, with anglers targeting calamari being generally more satisfied, although satisfaction increased for snapper when interacted with CPUE. Insights into angler behavior and key factors that influence angling satisfaction will ultimately provide a basis for formulating performance indicators to monitor and assess future angler satisfaction. More broadly, our study also provides guidance about how management interventions will impact angler satisfaction, therefore making it more likely that needs and concerns of recreational fishers are considered in decision making processes.

Reeling in joy: Untangling the link between satisfaction and motivation in recreational fishing - Ali Jalali; Justin D. Bell; Harry K. Gorfine; Simon D. Conron (Marine Policy, 2025)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Angling to Reach a Destination to Fish—Exploring the Land and Water Travel Dynamics of Recreational Fishers in Port Phillip Bay, Australia - Ali Jalali; Justin D. Bell; Harry K. Gorfine; Simon Conron; Khageswor Giri (Frontiers in Marine Science, 2022)
Recreational fishing is a popular pastime and multibillion dollar industry in Australia, playing a key economic role, especially in regional areas. In the State of Victoria, Port Phillip Bay (PPB), bordered by Melbourne and its suburbs, is the largest of the State’s marine recreational fisheries. At present, little is known about the spatial and temporal dimensions of angler travel from origins to destinations, and the applicability of such spatial knowledge in fisheries management. To address this lack of information we assessed spatiotemporal dynamics and patterns in fishing trips, based upon travel distances on land and water, to acquire insight into the spatial ranges over which anglers residing in various locations travel to fishing destinations in the environs of PPB. Data for each angler per fishing trip, from 6,035 boat-based creel surveys, collected at 20 boat ramps in PPB during a 10-year period from 2010 to 2019, were analyzed by applying geospatial modeling. Differences were observed in both land and water travel distance by region and popular target species, with anglers who launched from Bellarine region traveling further on land, and those who targeted snapper traveling further on water. It was also evident that most anglers resided within close proximity of PPB, often less than 50 km, although some anglers traveled long distances across the State to access fishing locations, particularly when targeting snapper. This work further highlights the importance of spatially explicit approaches to inform fisheries management by identifying users across different landscape and seascape scales, and out-of-region or State fishing trips, which may especially impact coastal communities and benefit local businesses.

Post‐release survival of recreationally caught snapper, Pagrus auratus , in Port Phillip Bay, south‐eastern Australia - D. GRIXTI; S. D. CONRON; A. MORISON (Fisheries Management and Ecology, 2010)
Snapper, Pagrus auratus (Forester), is an important recreational species in marine waters of Victoria, Australia. This study estimated survival for compulsorily released undersized P. auratus by holding fish in cages and tanks for 3 days. In all, 620 P. auratus caught by angling were assessed for post‐release survival and 200 additional fish were used as controls. The survival rate was greater for shallow‐hooked (97%) than deep‐hooked (48%) P. auratus . Post‐mortems showed that hooking injuries to the throat and/or gill area caused most deaths, while piercing of the heart also caused mortalities. Removing deeply ingested hooks decreased survival. To estimate survival of P. auratus across the Victorian fishery, this study’s results should be combined with estimates of shallow‐hooking rates in the fishery. Shallow‐hooking rate estimates would quantify the impact of the low survival rate found for deep‐hooked fish.